The long-term results and changing patterns of biological valves at the mitral position in contemporary practice in Japan - Abe, Tomonobu (Nagoya J Med Sci, 2016)
Mitral valve surgery has changed with the wide acceptance of mitral valve repair. The aim of this study is to obtain the long-term results of patients who underwent mitral valve replacement (MVR) using a biological prosthesis in contemporary practice in Japan. From January 1990 to December 2013, 76 patients underwent MVR using a biological prosthesis with or without concomitant surgery. Data were obtained by means of a questionnaire and a telephone interview. The mean follow-up period was 4.26 years. The etiologies of the patients included dilated cardiomyopathy (DCM) (n=20 [26.3%]), ischemic mitral regurgitation (n=7 [9.2%]). There is a trend towards decreasing number of rheumatic and degenerative disease and increasing number of DCM and ischemic mitral regurgitation. Three patients (3.9%) died in the perioperative period. The 5- and 10-year overall survival rates were 69.6% and 31.7%, respectively. The 5- and 10-year freedom from valve related death were 95.6% and 80.6 %, respectively. The linearized rates of valve-related complications were as follows: thromboembolism (0.63%/patient/year), bleeding (1.25%/patient/year). One patient underwent reoperation for structural degeneration 13 years after the first operation. The present study shows the long-term results of mitral valve replacement with bioproshtesis in a contemporary case series. The practice pattern is changing. The low rate of valve-related complication justify the current patient selection.